Impact of Digital Marketing on Aviation Businesses in Nigeria - Tiamiyu Hammed Olakulehin; Isaac Olayinka Afolayan; Josuha Olayemic Olagbemiro; Obasanjo James Babalola (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
The aviation industry encompasses almost all aspects of air travel and the activities that help to facilitate it. The blooming internet usage among the consumers has forced companies to target the market digitally. Social media marketing is a form of digital marketing that influences the power of widespread social media networks to reach the marketing and branding goals of the company. Airline industries are rigorously applying digital marketing tools and techniques to gain the ground among the competitors and serves as a crucial aspect for meeting consumer requirements and reinforce the relation among consumers in the airline industry. The study employed ex-post facto research design to analyze the impact of digital marketing on aviation businesses which will in turn lead to economic growth in Nigeria.  Data for the study were sourced from Nigeria Civil aviation Authority (NCAA).  The period of data collected covered for twenty-three years from 2000 to 2023. The results of the findings revealed that social media reach and website trafficking are stable in Nigeria, as all the variables seen by relatively high standard deviation. The outcome of the findings suggested that there are long run co-movement among aviation business and the e-ticketing among others as well as advert performance in Nigeria. Finally, there is a long-run causality jointly running from the digital marketing instruments at an adjustment speed of 25.74% annually.